Políticas públicas municipais de gestão ambiental-urbana: experiências institucionais na implementação de uma gestão plena em Santo André e Araraquara, SP - Novaretti, Diego Meleiro (2009)
The following work has as main purpose discuss the present public politics of urban environmental management by analyzing municipal models, practices and experiences, in search of an absolute management. Inside the thematic of environmental and urban institutional politics, dialoging with normative aspects, of planning and institutional management, this research seeks the understanding and the analysis of the urbanenvironmental management from the city councils of Araraquara and Santo André. The selection of these city counties parted from the observation that they are in a favorite position in comparison with other ones due to the operational, administrational and cultural circumstances respecting to the new demands from the National System of Environment. In parallel, this research will board the difficulties of these both city counties to attend the new establishes that are being placed to them since the redemocratization of the 80´s, with regard to the municipal urban-environmental management, as well as to the questions associated with the interface between the urban politics and the environmental politics.